If tan(A-B)/tan(A) + {sin(C)}^2 / {sin(A)}^2 = 1 Then Show that tan(A).tan(B)={tan(C)}^2 How can it be done? Thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by sovan tan(A).tan(B)={tan(C)}^2 tan(A) = {tan(x)}^2/tan(B) Replace in the initial equation .
Originally Posted by Aladdin tan(A) = {tan(x)}^2/tan(B) Replace in the initial equation . Substituting into the original equation should work. If you could use LaTeX tags next time, it sort of helps : If Then Show that How can it be done? Thanks
View Tag Cloud